Dinamika likuiditas bank mega syariah: studi analitis current ratio tahun 2020–2024 - Ningrum, Ajeng Rizqi; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze Bank Mega Syariah's liquidity level during the period 2020–2024 using the main liquidity ratio, namely the current ratio. This analysis was conducted to provide a comprehensive overview of Bank Mega Syariah's ability to meet its short-term obligations over the last five years. The data was obtained from Bank Mega Syariah's published annual financial reports, which were then processed to observe trends in changes in the current ratio and liquidity stability from year to year. The results of the analysis show the dynamics of liquidity performance, which are influenced by changes in the structure of current assets, funding growth, and the liquidity management strategies implemented by Bank Mega Syariah in response to fluctuating economic conditions. These findings contribute significantly to the understanding of Bank Mega Syariah's liquidity resilience and serve as a basis for evaluating the financial performance of Islamic banks, both for regulators, bank management, and academics.